An evaluation of the University of the Philippines College of Arts and Letters library collection and services based in UP CAL undergraduate students' library use - Lanticse, Jeralou A.; Gonzales, Grace Marie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
This study is about the evaluation of the University of the Philippines College of Arts and Letters (UP CAL) library collection and services. Respondents of this study are undergraduate students of UP CAL enrolled in 2nd semester AY 2011-2012. It aims to meet the following objectives: (1) to know if the collection and services of CAL library are efficient and effective in meeting the information needs of CAL students in every degree program; (2) to know what are the library collections that the library should enhance in order to meet the information needs of CAL students; (3) to determine the information needs of UP CAL students in every degree program; (4) to determine on how to improve the collection and services of UP CAL Library.
Of the 273 students determined respondents using Slovin's formula for this study, only 239 questionnaire were retrieved. Percentage was used to determine the number of respondents per degree program. A structured questionnaire was the main research tool for the survey. Respondents were selected randomly from different UP CAL "tambayans" and those who are visiting library.
After tabulating the data derived from the surveys, several conclusions and recommendations were made. General conclusions are as follows: (1) majority of the respondents are satisfied with its library hours, borrowing and lending hours of books and adequacy of library staff; (2) more than half of the respondents find clerical and routine tasks of librarians to be effective such as "lending and returning of books", "assisting in locating materials", and "book shelving", while less than half of the respondents find professional tasks of librarians to be effective; (3) majority of the respondents agreed that the librarians or library staff of UP CAL Library are helpful and effective; (4) majority of the respondents rated its library collection as "adequate" such as books, reference materials, magazines, theses and dissertations and database. The rest are rated as "just right"; (5) dictionaries and other general works are the most needed information by respondents.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- College of Arts and Letters Library -- Evaluation; University of the Philippines (Diliman) -- College of Arts and Letters Library -- Students; University of the Philippines (Diliman) -- College of Arts and Letters Library -- Use studies